PrPC as a Transducer of Physiological and Pathological Signals - Panes, Jessica D.; Saavedra, Paulina; Pineda, Benjamin; Escobar, Kathleen; Cuevas, Magdalena E.; Moraga-Cid, Gustavo; Fuentealba, Jorge; Rivas, Coralia I.; Rezaei, Human; Muñoz-Montesino, Carola (Frontiers in Molecular Neuroscience, 2021)
After the discovery of prion phenomenon, the physiological role of the cellular prion protein (PrPC) remained elusive. In the past decades, molecular and cellular analysis has shed some light regarding interactions and functions of PrPC in health and disease. PrPC, which is located mainly at the plasma membrane of neuronal cells attached by a glycosylphosphatidylinositol (GPI) anchor, can act as a receptor or transducer from external signaling. Although the precise role of PrPC remains elusive, a variety of functions have been proposed for this protein, namely, neuronal excitability and viability. Although many issues must be solved to clearly define the role of PrPC, its connection to the central nervous system (CNS) and to several misfolding-associated diseases makes PrPC an interesting pharmacological target. In a physiological context, several reports have proposed that PrPC modulates synaptic transmission, interacting with various proteins, namely, ion pumps, channels, and metabotropic receptors. PrPC has also been implicated in the pathophysiological cell signaling induced by β-amyloid peptide that leads to synaptic dysfunction in the context of Alzheimer’s disease (AD), as a mediator of Aβ-induced cell toxicity. Additionally, it has been implicated in other proteinopathies as well. In this review, we aimed to analyze the role of PrPC as a transducer of physiological and pathological signaling.